ANALISIS PENGARUH CURRENT RATIO, WORKING CAPITAL TURNOVER, DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET - Wenny Anggeresia Ginting (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
This study was conducted on property and real estate companies listed on the Indonesia Stock Exchange. The purpose of this research was to find out the effect of current ratio, working capital turnover, and total asset turnover partially and simultaneously on return on asset. The populations of this research were 47 property and real estate companies listed on Indonesia Stock Exchange from 2012 until 2015, and the 20 samples were drawn by purposive sampling technique. This research used secondary data and hypothesis testing was done by using multiple linear regression analysis. The result of determination coefficient test (adjusted R2) showed that simultaneously, the ability of current ratio variable, working capital turnover, and total asset turnover to explain the return on the asset was 40.1% while the remaining 59.9% was affected by other variables. The result of simultaneous research (test F), showed that current ratio, working capital turnover, and total asset turnover had a significant and positive effect on return on the asset in property and real estate companies listed in Indonesia Stock Exchange in the period of 2012-2015. Partially the result of research (t-test) showed that total asset turnover had a significant and positive effect on return on asset, while current ratio and working capital turnover did not have a significant effect on return on assets in property and real estate companies listed in Indonesia Stock Exchange in the period of 2012-2015.